AVALIAÇÃO DO PLANO DIRETOR COMO FERRAMENTA PARA A SUSTENTABILIDADE, NO MUNICÍPIO DE ROSÁRIO, ESTADO DO MARANHÃO - Medeiros, ângela Maria Ferreira de (2008)
A study aiming for evaluating the Rosário District Project Plan in Maranhão , (02°56 12,6 S 044°14 51,6 W) took place, in view of sustentability, wanting to investigate , if in fact, economic, social, environmental, cultural and institutional dimensions, which are considered the pillars of the sustentability, were being taken into consideration. The regulatory urban instruments of real state and the actions taken in municipal district planning were identified, evaluating their adequacy for Project Plan implementation, which were also investigated to which extent they were effective in popular participation and social control in all stages of the elaboration of the Project Plan. The methodology used was exploratory bibliography research, following a qualitative search approach, semi-structured questionnaires, interviews and image analysis of the use and occupations of the soil/ground. The public policies contemplated in the Project Plan were studied, evaluating if they are warrant of an administration that prioritizes the source of equity in environment sustentability that leads to the discussion for a social relations field and values community participation. The study concludes that the Project Plan is not in accordance with economic, social, environmental, cultural and institutional district reality, having nothing that assures district sustentability.